An Evaluation of Zakat Productive Program in the Pandemic - Nadia Putri; Mohamad Soleh Nurzaman (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2021)
Having the access of technology and information are some of the requirements needed to live in the middle of pandemic. On the other side, poverty is one of the main challenges that Islamic countries like Indonesia has to encounter. Because of the same reason, not everyone able to have the privilege to access nor master technology and information. However Islam offers the solution in the form of zakat to distribute the wealth and minimizing the gap of one’s economy and social status. This paper attempts to evaluate Sekolah Menengah Kejuruan Informatika Utama, program founded by Yayasan Baitul Maal PLN towards their students and alumni economy and social status. Using Social Return on Investment, this paper aims to provide a different perspective of zakat distribution run by Perusahaan Listrik Negara as Indonesia’s Public Company. The result then shows that SROI provides a financial measure of this value, that for every Rp.1 spent on SMKI Utama there is social value of Rp. 2.25 created over 1 year period.